Population pharmacokinetics and Bayesian estimators for intravenous mycophenolate mofetil in haematopoietic stem cell transplant patients. Issue 8 (28th February 2020) - Labriffe, Marc; Vaidie, Julien; Monchaud, Caroline; Debord, Jean; Turlure, Pascal; Girault, Stephane; Marquet, Pierre; Woillard, Jean‐Baptiste
Abstract : Aims: Intravenous mycophenolate mofetil (IV MMF), a prodrug of mycophenolic acid (MPA), is used during nonmyeloablative and reduced‐intensity conditioning haematopoetic stem cell transplantation (HCT) to improve engraftment and reduce graft‐versus‐host disease. The aims of this study were to develop population pharmacokinetic models and Bayesian estimators based on limited sampling strategies to allow for individual dose adjustment of intravenous mycophenolate mofetil administered by infusion in haematopoietic stem cell transplant patients. Methods: Sixty‐three MPA concentration–time profiles (median [min–max] = 6 [4–7] samples) were collected from 34 HCT recipients transplanted for 14 (1–45) days and administered IV MMF every 8 hours, concomitantly with cyclosporine. The database was split into development (75%) and validation (25%) datasets. Pharmacokinetic models characterized by a single compartment with first‐order elimination, combined with two gamma distributions to describe the transformation of MMF into mycophenolic acid, were developed using in parallel nonparametric (Pmetrics) and parametric (ITSIM) approaches. The performances of the models and the derived Bayesian estimators were evaluated in the validation set. Results: The best limited sampling strategy led to a bias (min, max), root mean square error between observed and modeled interdose areas under the curve in the validation dataset of −11.72% (−31.08%, 5.00%), 14.9% for ITSIM and −2.21% (−23.40%, 30.01%), 12.4% for Pmetrics with three samples collected at 0.33, 2 and 3 hours post dosing. Conclusion: Population pharmacokinetic models and Bayesian estimators for IV MMF in HCT have been developed and are now available online (https://pharmaco.chu-limoges.fr ) for individual dose adjustment based on the interdose area under the curve.